Flowable resin and marginal gap on tooth third medial cavity involving enamel and radicular cementum: A SEM evaluation of two restoration techniques - G Lo Giudice; M Cicciù; G Cervino; A Lizio; A M Visco (Indian Journal of Dental Research, 2012)
Purpose: The aim of this study is to investigate the presence and the extent of a possible marginal gap after the interposition of a flowable composite between the composite restoration and the dental structures (enamel and cementum). This technique is also used to eliminate the infiltration in a zone of the cavity preparation that is frequently at a risk of secondary decay. Materials and Methods: Fifteen human premolars extracted for orthodontic reasons were used for the study. A cavity with mesial and distal margin in enamel and cementum was realized in every tooth. The cavities were then restored with an adhesive system (ScotchBond 3MÔ) and composite (Filtek Supreme 3MÔ); and, a fine layer of flowable composite was applied in the distal margin of each cavity. Scanning electron microscopy (SEM) in secondary electron imaging (S.E.I.) modality was used for the study and identifying the marginal gaps in the composite restorations. Data was investigated on the mesial and distal margin of each cavity at the restoration-enamel interface, and at the restoration-cementum interface. The interfaces were divided in four groups: Group A (enamel/composite); Group B (enamel/flow/composite); Group C (cementum/composite); and, Group D (cementum/flow/composite). Results: By the comparison of the gap′s average width found in each group, it is evidenced that the average width of the gap increases when the interface moves from the coronal to the radicular end (Group A 0,1 ± 0,4 μm Vs Group C 12,3 ± 11,6 μm; Group B 0,2 ± 0,8 μm Vs Group D 2,8 ± 6,6 μm). Correlating the measurements of the marginal gap′s average width among the Group A and Group B, no significant variations were obtained; and instead, on comparing Group C with Group D, the gap′s average width decreases. Conclusion: The interposition of a low elastic modulus composite between the adhesive layer and the composite resin allows an improvement of the cementum-restoration interface by the means of a lower shrinkage stress during polymerization.